2015
DOI: 10.1371/journal.pone.0137019
|View full text |Cite
|
Sign up to set email alerts
|

A COLQ Missense Mutation in Sphynx and Devon Rex Cats with Congenital Myasthenic Syndrome

Abstract: An autosomal recessive neuromuscular disorder characterized by skeletal muscle weakness, fatigability and variable electromyographic or muscular histopathological features has been described in the two related Sphynx and Devon Rex cat breeds (Felis catus). Collection of data from two affected Sphynx cats and their relatives pointed out a single disease candidate region on feline chromosome C2, identified following a genome-wide SNP-based homozygosity mapping strategy. In that region, we further identified COLQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Many syndromes resembling but distinct from MG have been recognized in dogs and cats since 1974. 1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][59][60][61][62][63][64][65][66][67][68][69][70][71] Affected dogs and cats also manifest skeletal muscle weakness and fatigability, but NMJ autoantibody testing for AChRs is negative. Table 3).…”
Section: Congential Myasthenic Syndromesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many syndromes resembling but distinct from MG have been recognized in dogs and cats since 1974. 1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][59][60][61][62][63][64][65][66][67][68][69][70][71] Affected dogs and cats also manifest skeletal muscle weakness and fatigability, but NMJ autoantibody testing for AChRs is negative. Table 3).…”
Section: Congential Myasthenic Syndromesmentioning
confidence: 99%
“…12,13 These CMSs involve a mutation in the collagen-like tail subunit of asymmetric acetylcholinesterase (COLQ) gene, which anchors acetylcholinesterase (AChE) to the basal lamina of the NMJ. 8,10,12,13 In Labrador Retrievers, it is caused by a nonsynonymous mutation in exon 14, and is inherited in an autosomal recessive manner. 8 Reported onset is 2 to 3 weeks of age, electromyography (EMG) is normal, and a decremental response is observed upon RNS.…”
Section: Synaptic Cmssmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a single report of two mongrel dogs with suspected CMS; however, confirmatory diagnostic testing was not performed ( 10 ). CMS has also been reported in Sphynx and Devon Rex cats as well as Brahman calves ( 11 13 ). To the authors’ knowledge, this is the first report describing a confirmed case of CMS in a mixed breed animal.…”
Section: Discussionmentioning
confidence: 83%
“…A CHRNE mutation was also identified as the cause of CMS in Brahman calves ( 13 ). CMS in Labrador Retrievers and Sphynx and Devon Rex cats is the result of a mutation in the COLQ gene, which encodes the collagenous tail of acetylcholinesterase (AChE) ( 5 , 6 , 8 , 11 , 12 ). In the Old Danish Pointing dog breed, however, CMS is associated with pre-synaptic dysfunction of neuromuscular transmission and a mutation in the choline acetyl-transferase ( CHAT ) gene ( 6 ).…”
Section: Discussionmentioning
confidence: 99%